COLLECTIVE MEMORY ON THE POLITICAL VIOLENCE OF SCHOOLCHILDREN BELONGING TO POPULAR SECTORS IN METROPOLITAN LIMA - TICONA FERNÁNDEZ-DÁVILA, Ruben (2023)
The experience of political violence in Peru generated, among other consequences, a profound gap in the relationship between the history taught and the processes of consolidation of historical memory and identity; being that the school is a public space where memory is built. Its present possibilities and limitations are related to the teaching of the recent and living past. For the purposes of this research, we intend to analyze the contents of the history books that are taught in schools in Peru and the collective memory about the period of political violence in students at public schools in the 5th year of secondary education. Methodologically is a longitudinal study covering the years 2013 - 2020, will make use of a mixed approach, which  will combine both the quantitative analysis through the surveys to be applied, as well as qualitative analysis based on in-depth interviews, from a selected sample of Metropolitan Lima schoolchildren In addition, a content analysis of the history textbooks of Peru in the fifth year of secondary education will be carried out